2021
DOI: 10.1038/s41590-021-00942-0
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I triggers a signaling-abortive anti-SARS-CoV-2 defense in human lung cells

Abstract: Efficient immune responses against viral infection are determined by sufficient activation of nucleic acid sensor-mediated innate immunity 1,2 . Coronavirus disease 2019, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains an ongoing global pandemic. It is an urgent challenge to clarify the innate recognition mechanism to control this virus. Here we show that retinoic acid-inducible gene-I (RIG-I) sufficiently restrains SARS-CoV-2 replication in human lung cells in a type I/III inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
164
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(183 citation statements)
references
References 52 publications
6
164
0
1
Order By: Relevance
“…In Calu-3 cells, RIG-I was largely dispensable for the antiviral cytokine response to infection. While our study was in preparation, other manuscripts reported that MDA5 and its adaptor MAVS recognise SARS-CoV-2 infection 19 , 20 , 24 , 34 . Three of these reports 19 , 20 , 24 included siRNA-mediated knockdown and/or genetic ablation in Calu-3 cells.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In Calu-3 cells, RIG-I was largely dispensable for the antiviral cytokine response to infection. While our study was in preparation, other manuscripts reported that MDA5 and its adaptor MAVS recognise SARS-CoV-2 infection 19 , 20 , 24 , 34 . Three of these reports 19 , 20 , 24 included siRNA-mediated knockdown and/or genetic ablation in Calu-3 cells.…”
Section: Discussionmentioning
confidence: 81%
“…While our study was in preparation, other manuscripts reported that MDA5 and its adaptor MAVS recognise SARS-CoV-2 infection 19 , 20 , 24 , 34 . Three of these reports 19 , 20 , 24 included siRNA-mediated knockdown and/or genetic ablation in Calu-3 cells. In contrast to these three studies and to our work, another study found that both MDA5 and RIG-I sense SARS-CoV-2 infection in Calu-3 cells, and that upregulation of the pro-inflammatory cytokine IL6 was uncoupled from MDA5, but dependent on RIG-I and MAVS 21 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The innate immune system utilizes host-encoded nucleic acid sensors, known as the pattern recognition receptors (PRRs), to surveil viral pathogens by detecting their pathogen-associated molecular patterns (PAMPs) 7 . Following SARS-CoV-2 infection, multiple cytosolic PRRs, including RIG-I, MDA-5, and LGP2, mediate viral RNA recognition in infected lung epithelial cells and initiate front-line antiviral defense through the production of IFN-I 8,9 . Upon secretion, IFN-I engages with its universally expressed receptor in autocrine and paracrine fashions, stimulating the expression of a large network of interferon stimulated genes (ISGs) to inhibit viral replication, and cytokines and chemokines to recruit specialized immune cells to sites of infection.…”
mentioning
confidence: 99%